A experiência educativa como espaço de (trans)formação profissional - Vieira, Flávia (Linguarum Arena, 2018)
The present paper advocates the centrality of experience in the process of professional transformation. With reference to a post-graduate course that articulates language education with pedagogical supervision, an approach is proposed where trainee teachers are the main actors in knowledge construction and educational change. In this approach, profissional didactics is the axis for the development of teacher education. Through self-questioning and professional empowerment, and by putting research in the service of pedagogy, teachers explore the space between real and ideal, thus interrogating and reconstructing the meaning of educational experience. From this perspective, professional didactics is didactics-in-motion. It cannot be dissociated from re-signifying experience and is always transitional and unfinished.